Following in parental footsteps? The influence of gender and learning experiences on entrepreneurial intentions. (September 2019) - Bloemen-Bekx, Mira; Voordeckers, Wim; Remery, Chantal; Schippers, Joop
This study focusses on the influence of the family context on the development of entrepreneurial intention (EI) among young adults with entrepreneurial parents. It extends the EI literature by drawing on social cognitive career theory to study the interaction between entrepreneurial parents and their children. We introduce the learning experiences 'vicarious learning' and 'social persuasion' as antecedents of EI and found significant empirical support for the influence of social persuasion. In addition, we study the relationship between gender and EI. Our results not only confirm the direct effect of gender on EI but also reveal a significant mediating effect of parental preference – one of the social persuasion factors studied – on the gender–EI relationship.